Pengaruh Sistem Pendukung Keputusan untuk Pemilihan Laptop dengan Menggunakan Metode Simple Multi Attribute Rating Technique (SMART) - Angely Mutiara Butar Butar; Rektor Sianturi; Christa Voni Roulina Sinaga (Bulletin of Community Engagement, 2024)
Choosing a technological device such as a laptop is an important decision for students, especially in supporting their academic activities. This research aims to apply the Simple Multi Attribute Rating Technique (SMART) method in a decision support system for selecting laptops, which can help students determine which laptop suits their needs. This SMART method considers various important attributes in selecting a laptop, such as price, performance, battery life and portability. The decision support system developed can provide recommendations that are objective and measured based on the preferences and priorities of each student. With this system, it is hoped that students can make better and more efficient decisions in choosing a laptop that suits their academic needs. The data collection technique used was distributing questionnaires. The research results show that the Asus E410KA is in first place with a final score of 0.972, followed by the Elitebook cellphone in second place with a score of 0.375, the 14S cellphone in third place with a score of 0.366, and the Acer Aspire A14 in fourth place with a score of 0.313. This decision support system not only helps students in the selection process, but can also increase their understanding of the important specifications and features of a laptop. In addition, the SMART method can be adapted to suit the needs of selecting other technology products, such as smartphones or tablets, which are also often used by students in academic activities. Using a system like this can also help reduce the confusion and anxiety that students often experience when faced with the many laptop choices on the market